In vitro antioxidant activity of rice protein affected by alkaline degree and gastrointestinal protease digestion. (25th July 2016) - Liu, Ye; Wang, Zhengxuan; Li, Hui; Liang, Mingcai; Yang, Lin
Abstract: BACKGROUND: To elucidate whether and how alkali treatment, which is a common process for rice protein (RP) extraction, affects antioxidant activity of RP, the different degree of alkali (from 0.1% to 0.4% of NaOH) was used to extract RP (RP‐1, RP‐2, RP‐3, RP‐4). RESULTS: The antioxidant capacities of scavenging free radicals [2, 2′‐azinobis(3‐ethylbenzothiazoline‐6‐sulfonic acid] diammonium salt, ABTS; 1, 1‐diphenyl‐2‐picrylhydrazyl, DPPH), chelating metals (iron, copper) and reducing power investigated in the hydrolysates of RPs (RP‐1, RP‐2, RP‐3, RP‐4) during in vitro pepsin–pancreatin digestion were effectively affected by alkali treatment. The present study demonstrated that the weakest antioxidant responses to ABTS radical‐scavenging activity, DPPH radical‐scavenging activity, iron chelating activity, copper chelating activity and reducing power were produced by RP‐4 extracted by the highest alkali proportion (0.4% NaOH). CONCULSION: The present study indicates that antioxidant capacity of RP could be more readily depressed by strict alkali degree and affected by gastrointestinal proteases. Results suggest that alkali extraction is a vital process to regulate the antioxidant activity of RP through modifying the compositions of amino acids, which are dependent on alkali magnitude. © 2016 Society of Chemical Industry